Evaluation of heat transfer during the process of heating water in containers using a solar cooker box-type. Issue 1 (January 2021) - Terres, H; Chávez, S; Lizardi, A; Alvarez, E
Abstract: This work presents the experimental results and the evaluation of the heat transfer mechanisms by conduction, convection, and radiation that occur during the water heating process inside four containers with volumes of 250, 500, 750, and 1000 ml. using as for this process a box-type solar cooker. For the experimental measurements, a type k thermocouple arrangement was used, located in the water, the exterior surfaces of the containers, and the glass that forms part of the solar cooker cover. For the acquisition of the data perceived by the thermocouples, a Compact Field Point from National Instruments was implemented and for the measurement of global solar radiation, an Eppley 8-48 radiometer was used. The results obtained from the evaluation show that the most important heat transfer mechanism is by conduction located in the exterior glass of the solar cooker cover and the convection heat transfer in this same glass is the one with the lowest values. The evaluation of the results achieved contributes to the knowledge of the operation of solar cookers, which can contribute to the design and improvements of these solar energy devices.